1993
DOI: 10.1101/gad.7.12a.2446
|View full text |Cite
|
Sign up to set email alerts
|

Amino-terminal amino acids modulate sigma-factor DNA-binding activity.

Abstract: Prokaryotic transcription initiation factor cr is required for sequence-specific promoter recognition by RNA polymerase. Genetic studies have indicated that ¢r itself interacts with DNA at the -10 and -35 promoter consensus sequences. Binding of Escherichia coli ¢r 7° to DNA in vitro, however, can only be observed for truncated polypeptides lacking the amino-terminal amino acids. We have investigated the role of the amino terminus of E. coli ¢r 7° in controlling DNA-binding ability. Deletion analysis indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
202
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(213 citation statements)
references
References 29 publications
9
202
2
Order By: Relevance
“…We d o not want to emphasize the p-structure (Table 1) that was generated in the mutant protein as any estimation from very low intense CD bands is susceptible to error. Fluorescence studies with l-anilinonapthalene-8-sulphonate, however, indicate that both N-terminal and C-terminal mutations in 07" expose similar hydrophobic surfaces for the probe and they were buried in native 07 '. We have mentioned before that interaction of the N-terminal portion of 07" with the promoter-binding regions at the C-terminal end is responsible for masking the DNA-binding ability of free a7" (Dombroski et al, 1993). We proposed a model earlier where it was speculated that Trp434 at the junction of the 2.31 2.4 subdomain in 0 " interacts with the hydrophobic pockets at the N-terminal domain (Gopal e t al., 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We d o not want to emphasize the p-structure (Table 1) that was generated in the mutant protein as any estimation from very low intense CD bands is susceptible to error. Fluorescence studies with l-anilinonapthalene-8-sulphonate, however, indicate that both N-terminal and C-terminal mutations in 07" expose similar hydrophobic surfaces for the probe and they were buried in native 07 '. We have mentioned before that interaction of the N-terminal portion of 07" with the promoter-binding regions at the C-terminal end is responsible for masking the DNA-binding ability of free a7" (Dombroski et al, 1993). We proposed a model earlier where it was speculated that Trp434 at the junction of the 2.31 2.4 subdomain in 0 " interacts with the hydrophobic pockets at the N-terminal domain (Gopal e t al., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding core RNA polymerase, the DNA-binding domains in a are unmasked and the resulting holoenzyme recognizes the promoter sequence with the help of 07" to initiate promoter-specific transcription. Dombroski et al (1993) showed that the N-terminal 1.1 subdomain of 07" preferentially inhibits DNA binding by domain 4 of 07" in trans, in comparison to that by domain 2.…”
mentioning
confidence: 99%
“…Discussion Region 1.1, the negatively-charged domain found at the N terminus of primary factors, such as 70 , is known to serve several important roles. In free 70 , the presence of this region prevents recognition of promoter DNA (53,54). In holoenzyme, region 1.1 lies within a channel of core polymerase that will interact with dsDNA downstream of the transcription start site upon formation of the stable promoter/polymerase complex (36).…”
Section: Figmentioning
confidence: 99%
“…The transcription factors evolutionarily related to Escherichia coli 70 are subdivided into two groups (15). The primary factor is required for the expression of housekeeping genes whose products are essential for exponential cell growth.…”
mentioning
confidence: 99%